Sevoflurane Therapy for Severe Refractory Bronchospasm in Children. Issue 8 (August 2016) - Palacios, Alba; Mencía, Santiago; Llorente, Ana M.; Cruz, Jaime; Toledo, Blanca; Ordóñez, Olga; Olmedilla, Marta; Lopez-Herce, Jesus
Abstract : Objectives: To describe the effect of inhaled sevoflurane in the treatment of severe refractory bronchospasm in children. Design: Retrospective case series. Setting: Two PICUs of tertiary general university hospitals in Spain. Patients: Ten patients ranging from 5 months to 14 years old with severe bronchospasm and acute respiratory failure requiring tracheal intubation and mechanical ventilation and treated with sevoflurane from 2008 to 2015. Intervention: Inhaled sevoflurane therapy was initiated after failure of conventional medical management and mechanical ventilation. In two patients, sevoflurane was administered through a Servo 900C ventilator (Maquet, Bridgewater, NJ) equipped with a vaporizer and in the other eight patients via the Anesthetic Conserving Device (AnaConDa; Sedana medical, Uppsala, Sweden) with a critical care ventilator. Measurements and Main Results: Inhaled sevoflurane resulted in statistically significant decreases of PaCO2 of 34.2 torr (95% CI, 8.3–60), peak inspiratory pressure of 14.3 cm H2 O (95% CI, 8.6–19.9), and improvement in pH of 0.17 (0.346–0.002) within 6 hours of administration. Only one patient presented hypotension responsive to volume administration at the beginning of the treatment. All patients could be extubated within a median time of 120 hours (interquartile range, 46–216). Conclusions: Inhaled sevoflurane therapy decreases the levels of PaCO2 and peak inspiratory pressure values, and it may be considered as a rescue therapy in patients with life-threatening bronchospasm refractory to conventional therapy.